Exploring the Interrelations between codes of conduct and financial performance: Evidence from Greece - Panagiotis Kyriakogkonas; Spyridon Alexiou (SPOUDAI - Journal of Economics and Business, 2017)
Despite the fact that numerous studies have been conducted exploring possible relationship between corporate social responsibility and profitability, there is no research focusing on the relationship between code of conduct and financial performance. For this reason, the following research focuses at codes of conduct and examines whether exists any kind of relationship between codes of conduct and financial performance. In order to succeed in that, we execute multiple regressions. Moreover, we investigate the situation in Greece in 2014, regarding codes of conduct compliance, content and numerous other qualitative elements, by using as a sample the listed in Athens Stock Exchange industrial and commercial companies. In order to succeed in that, we sent a questionnaire to internal audit managers addressing all important elements regarding codes of conduct. Our results revealed no statistically significant relation between codes of conduct and financial performance. Moreover, our research contains useful conclusions regarding the situation in listed in Athens Stock Exchange companies about codes of conduct.
Keywords: M19; 330; code of conduct; corporate social responsibility; financial performance